The Commemoration of Independence Day: Recalling Indonesian Traditional Games - Fitri, Mustika; Nur, Hana Astria; Putri, Wulandari (Frontiers in Psychology, 2020)
Traditional games in Indonesia is one of cultural heritages that the existence should be protected and preserved. The purpose of this study was to preserve the cultural diversity by recalling the traditional games through the commemoration of Indonesia Independence Day that is conducted annually. The Online Ethnography method was used in this research by administering text analysis and interview. The result of the study showed that the traditional games held in the commemoration of Independence Day of Republic of Indonesia indirectly built a bonding of the people. Furthermore, as a form of cultural diversity, where every region has different names and rules of the traditional games, the games build the togetherness, cooperation, and solidarity among the member of the society.